Literasi Digital Guru Pendidikan Agama Islam Berstatus Pegawai Negeri Sipil (PNS) dalam Pembelajaran Pendidikan Agama Islam di MTsN 1 Hulu Sungai Tengah dan MTsN 3 Hulu Sungai Tengah - Rizky Fauzan Hasni (Universitas Maritim AMNI Semarang, 2024)
Digital literacy is the ability to obtain, understand, and use information based on various digital sources. Information and communication technology development was increasing rapidly, and the Republic of Indonesia Constitution number 14 year 2005 demanded professional teachers be able to utilize digital technology and assess the validity of information from digital sources. Gilster said there are four aspects of digital literacy competence: internet searching, guidance of hypertext, evaluation of information content, and knowledge assembly. The researcher focuses on the problem of the digital literacy ability of Islamic education teachers and civil servants in Islamic education learning. The type of this research is field research with descriptive and qualitative approaches, which did not produce statistical analysis procedures or quantification methods. However, the research was analyzed through illustrations, narrative and interpretive words. Data collection was carried out through interviews, observation, and documentation. The research results showed that: First, based on the internet searching for Islamic Education teachers at MTsN 1 Hulu Sungai Tengah and MTsN 3 Hulu Sungai Tengah can search the information on the internet using search engines. Second, the ability to guide hypertext or hypertextual navigation of Islamic Education teachers at MTsN 1 Hulu Sungai Tengah and MTsN 3 Hulu Sungai Tengah still require a deeper understanding. Third, based on the ability to evaluate the information content of Islamic Education teachers at MTsN 1 Hulu Sungai Tengah and MTsN 3 Hulu Sungai Tengah, Islamic Education teachers still need to be more critical of the information that they find on the internet. Fourth, the ability to have a knowledge assembly for Islamic Education teachers at MTsN 1 Hulu Sungai Tengah and MTsN 3 Hulu Sungai Tengah also still needs deeper knowledge and understanding. Fifth, the ways implementation of digital literacy in the learning process of Islamic Education are using a computer laboratory, a laptop, and LCD to convey the information or material from the internet.